Grouting in rock tunnels by data mining 2 - Lim, Kai Jian (Nanyang Technological University, 2023)
In rock tunnelling, it is common to encounter water seepage issues, especially for areas with high groundwater tables. Grouting is commonly used by engineers to limit water seepage. The grouting techniques used are predominantly empirical, with some developments in theoretical and analytical approaches. However, these developments are mostly idealistic in nature and are not widely adopted. Therefore, a more efficient method for guidance in grouting works is needed. Conversely, engineering data collected during civil works often remain underutilised.